2015
DOI: 10.1103/physrevb.91.144508
|View full text |Cite
|
Sign up to set email alerts
|

General framework for transport in spin-orbit-coupled superconducting heterostructures: Nonuniform spin-orbit coupling and spin-orbit-active interfaces

Abstract: Electronic spin-orbit coupling (SOC) is essential for various newly discovered phenomena in condensed-matter systems. In particular, one-dimensional topological heterostructures with SOC have been widely investigated in both theory and experiment for their distinct transport signatures indicating the presence of emergent Majorana fermions. However, a general framework for the SOC-affected transport in superconducting heterostructures, especially with the consideration of interfacial effects, has not been devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 107 publications
0
22
0
Order By: Relevance
“…The calculated conductance features of SOC [42][43][44][45][46] can be distinguished from k-independent spin-flip scattering by magnetic moments: For Z ¼ 0 SOC always reduces the conductance and the subgap conductance vanishes for P ¼ 1. In contrast, k-independent spin-flip scattering [47] can increase the conductance and the subgap conductance is in general finite for P ¼ 1.…”
mentioning
confidence: 97%
“…The calculated conductance features of SOC [42][43][44][45][46] can be distinguished from k-independent spin-flip scattering by magnetic moments: For Z ¼ 0 SOC always reduces the conductance and the subgap conductance vanishes for P ¼ 1. In contrast, k-independent spin-flip scattering [47] can increase the conductance and the subgap conductance is in general finite for P ¼ 1.…”
mentioning
confidence: 97%
“…An interesting expansion of the present work would be to explore how magnetic interfaces232425 and spin-orbit coupling would influence the proximity-gap phase diagram and topological properties of multiterminal Josephson junctions, as recent works have demonstrated that in particular the latter of these can induce several novel effects in both diffusive and ballistic superconducting hybrids13262728293031323334.…”
Section: Resultsmentioning
confidence: 99%
“…While strong hints of MF physics have been highlighted in Ref. [Mourik et al, 2012], other recent articles [Churchill et al, 2013;Linder et al, 2010;Kells et al, 2012;and Sun and Shah, 2015] offer alternative interpretation of the observed zero bias anomaly in terms of Kondo physics. Therefore an unambiguous "smokinggun" experimental proof of the presence of MFs still has to come.…”
Section: B Diffusive Limit: Weak Anti-localizationmentioning
confidence: 99%